Guideline for the analysis of the microbial communities of the human upper airways. Issue 1 (31st December 2022) - Mancabelli, Leonardo; Ciociola, Tecla; Lugli, Gabriele Andrea; Tarracchini, Chiara; Fontanta, Federico; Viappiani, Alice; Turroni, Francesca; Ticinesi, Andrea; Meschi, Tiziana; Conti, Stefania; Ventura, Marco; Milani, Christian
ABSTRACT: The recent COVID-19 pandemic prompted a rapid-growing interest in the investigation of the human microbiota of the upper airways. In fact, the resident microbial community of this body district may have an influence on the onset of SARS-CoV-2 infection and its clinical course in terms of presence, symptom severity, and outcomes. However, several microbiological methodologies are available to study the human microbiota, reflecting the extensive fragmentation of methodological approaches. We investigate the impact of two critical steps that can induce biases in the downstream analyses, i.e. sampling method and microbial DNA extraction kit employed. We observed major discrepancies regarding the total amount of prokaryotic DNA that could be retrieved from a biological sample and the proportion between bacterial DNA and human host DNA. Moreover, shotgun DNA sequencing and taxonomic profile reconstruction also revealed correlations between sampling methods and the procedures applied for microbial DNA extraction. Based on all the data collected in this study, we formulate indications regarding the most efficient and reliable methodological procedures for the metagenomic analyses of the upper airways' microbiota to maximize accuracy and reproducibility.